miRNA-223 regulates ischemic neuronal injury by targeting the type 1 insulin-like growth factor receptor (IGF1R) - Feng, She-Jun; Zhang, Xue-Qiang; Li, Jun-Tao; Dai, Xiao-Min; Zhao, Fei (Folia Neuropathologica, 2018)
Cerebral ischemia injury seriously endangers human health and its molecular mechanism is still not fully understood. microRNA-223 (miR-223) has been reported to be involved in many physiological functions but the specific role of miRNA-223 in ischemic neuronal injury is still unclear. An oxygen-glucose deprivation and simulated reperfusion (OGD/R) model was constructed here to investigate the possible role miR-223 played in ischemic neuronal injury. The expression of miRNA-223 in the OGD/R model and its effect on cell proliferation were studied by qPCR and CCK8 assay. We observed that miR-223 was significantly over-expressed after OGD/R treatment and it suppressed significantly cortical neurons proliferation. To further study the mechanism involved, we predicted and examined the potential targets of miR-223 by targetscan, qPCR, western blot and luciferase reporter assay. We found that the expression level of type 1 insulin-like growth factor receptor (IGF1R) was negatively associated with the level of miR-223. Furthermore, the relative luciferase activity of pmirGLO-WT was inhibited obviously, while no significant change was observed in the pmirGLO-Mut group, indicating that miR-223 could bind to IGF1R. Similar cell proliferation suppression caused by miR-223 antagomir was observed when IGF1R was silenced. On the contrary, when cortical neurons were co-treated with miR-223 agomir and the cDNA of IGF1R which did not contain 3’- untranslated region, the inhibition caused by miR-223 disappeared. Our results suggested that miR-223 may suppress proliferation of cortical neurons that were treated with OGD/R via inhibiting IGF1R expression.